Life-cycle assessment of residential buildings - Mateus, Ricardo (2011)
The quantification of the environmental impacts of a building can help decisionmakers to identify processes of major environmental impacts. Therefore it can be used since the early stages of design to support decision makings which aim to promote lower environmental impacts and, as a result, more sustainable buildings. Life Cycle Assessment (LCA) is considered the most adequate method for evaluating the environmental pressure caused by materials, building assemblies and the whole life-cycle of a building. Nevertheless this method is not widely used in the building sector. This paper aims to present the main constrains that are hindering the use of LCA in the building sector. Moreover, it presents a solution to overcome the indentified barriers and to promote the use of LCA methods since the earlier phases of the design process.